2015
DOI: 10.1371/journal.pone.0131329
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Three Prognostic Models in Patients with Cancer in Need of Intensive Care in a Medical Center in China

Abstract: ObjectiveThe aim of this study was to evaluate the performance of Acute Physiology and Chronic Health Evaluation II (APACHE II), Simplified Acute Physiology Score 3 (SAPS 3), and Acute Physiology and Chronic Health Evaluation IV (APACHE IV) in patients with cancer admitted to intensive care unit (ICU) in a single medical center in China.Materials and MethodsThis is a retrospective observational cohort study including nine hundred and eighty one consecutive patients over a 2-year period.ResultsThe hospital mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
8
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 28 publications
7
8
2
4
Order By: Relevance
“…The APACHE II scoring system is an accurate measurement of clinical severity and correlates strongly with outcome in critically ill patients [21]. Consistent with our results, previous studies demonstrated effectiveness of APACHE II score for predicting in-hospital mortality of critically ill patients with cancer in need of intensive care [22,23]. Our findings emphasize that the prognosis of cancer patients is determined by severity at the time of RRT activation regardless of malignancy status.…”
Section: Discussionsupporting
confidence: 90%
“…The APACHE II scoring system is an accurate measurement of clinical severity and correlates strongly with outcome in critically ill patients [21]. Consistent with our results, previous studies demonstrated effectiveness of APACHE II score for predicting in-hospital mortality of critically ill patients with cancer in need of intensive care [22,23]. Our findings emphasize that the prognosis of cancer patients is determined by severity at the time of RRT activation regardless of malignancy status.…”
Section: Discussionsupporting
confidence: 90%
“…In a study by Ulus et al, APACHE II was reported to be successful in determining the mortality rate in 100 patients with respiratory failure . In a similar study by Xing et al, SAPS III was found to be good in respect of discrimination and calibration, and good in the prediction of mortality in patients with respiratory system diseases and pneumonia . In the current study, SAPS III and APACHE IV were successful in terms of discrimination and calibration ability and highly successful in terms of estimating the SMR and mortality rates in the group of respiratory system diseases, including pneumonia patients, whereas APACHE II did not show the same success.…”
Section: Discussionsupporting
confidence: 73%
“…In a study by Chan et al, APACHE IV was found to be inadequate for predicting mortality in abdominal sepsis patients (12). In a study by Xing et alin which patients were separated into diagnosis groups, SAPS III was determined to have excellent discrimination and calibration capabilities and fairly good mortality accuracy in sepsis patients (13). In the present study, the discrimination capability of all the scoring systems was found to be average but the calibration was found to be very good in the sepsis patients group.…”
Section: Discussionmentioning
confidence: 99%
“…In critically ill cancer patients, Soares, et al [4] observed that discrimination was good using SAPS-3 and SAPS-3 CSA models. Recently, Xing, et al [5] validated APACHE-II, APACHE-IV, and SAPS-3 models. Authors found that the performance of the three models was good.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer patients account for 13-18% of patients admitted to intensive care units (ICU) [2,3]. General predictive models have been evaluated in cancer patients admitted to ICU [4,5]; however, generalization is difficult because of the limitations of studies.…”
Section: Introductionmentioning
confidence: 99%